Suspected Placenta Accreta: Using Imaging to Stratify Risk of Morbidity - Matthews, Kathy C.; Fields, Jessica C.; Chasen, Stephen T. (American Journal of Perinatology, 2020)
Objective This study was aimed to compare clinical outcomes and use of interventions in women with suspected accreta based on the degree of antenatal suspicion.Study design This was a retrospective cohort study of women with suspected accreta from 2007 to 2019. Included patients had one or more imaging studies suggestive of accreta. Cases were classified as “lower risk” if imaging showed possible signs of accreta including mild or superficial myometrial infiltration, an abnormal uterine contour, an abnormal uteroplacental interface, or loss of the retroplacental hypoechoic zone and “higher risk” if there was clear evidence of more than superficial myometrial infiltration, placental tissue extruding beyond the uterine serosa, bridging vessel(s), or placental lacunae with high velocity and/or turbulent flow. The primary study outcome was a composite maternal morbidity including cesarean hysterectomy, transfusion of blood or blood products, unintentional cystotomy, or intensive care unit (ICU) admission. Chi-square, Fisher's exact test, and Mann–Whitney U-test were used for analysis.Results A total of 78 women had a suspected accreta on imaging, 36 with “lower risk” features and 42 with “higher risk” features. There were no differences in baseline maternal demographics. Women in the “higher risk” group were more likely to have a placenta previa (p < 0.01) and preoperative consultation with gynecologic oncology (p = 0.04). There was a significant difference in composite maternal morbidity between patients with “lower risk” and “higher risk” features of accreta on imaging (50 vs. 92.9%, p < 0.01). Median gestational age at planned and actual delivery were earlier in the “higher risk” group (36.6 vs. 34.9 weeks, p < 0.01; 36.0 vs. 34.7 weeks, p < 0.01).Conclusion Stratification of women with suspected accreta based on imaging corresponded to rates of maternal morbidity and operative complications, and appears to have been used clinically in selecting timing of delivery and interventions.Key Points
Keywords: abnormal placentation; accreta; increta; morbidly adherent placenta; percreta; placenta accreta spectrum